Study on The Organizational Culture That Drive Success for Start-up Young Entrepreneurs in Jakarta - Aristo Surya Gunawan; Ati Cahayani (Publikasi Indonesia, 2025)
Start-ups in Indonesia have grown fast for the last few years and have become first in Southeast Asia and ranked third in the world. However, this start-up failure rate is very high during their early stage. This is due to the instability of the business, which raised concerns regarding organizational culture. This study will continue the previous study from (A. S. Gunawan & Cahayani, 2025) By examining the culture of organizations that influences business achievement among young start-up entrepreneurs in Jakarta, this study uses quantitative and qualitative data. The quantitative data were collected through the dissemination of questionnaires and analysed using the mean score technique, whereas the qualitative data were gathered through interviews and interpreted using content analysis. The result showed that attention to detail, innovation, and risk-taking emerge as the prominent organizational culture characteristics that respondents believe as the driving factors for their business success.